Risk factors for college students’ online lending between different genders-A cross-sectional study in China - Zhang, Yan; Luo, Lun; Li, Pan; Xu, Yun; Chen, Zi (Frontiers in Psychology, 2023)
Background Online lending on campus is given more attention by researchers as its prominent adverse effects on students. The deficiencies of the previous studies on its psychological factors and intervention strategies were only based on qualitative research. Moreover, there is no study on gender differences. Therefore, our study aims to analyze the gender differences in psychological risk factors and give some practical suggestions for the intervention by quantitative methods. Method This is a cross-sectional survey among medical college students in Chengdu. A total of 984 effective questionnaires were collected. The questionnaire includes demographic data, monthly expenses, self-evaluation for three central psychology causing online lending based on empiricism (conformity, comparison, and hedonism), and three psychological assessment instruments (the Chinese version of the Satisfaction with Life Scale, Egna Minnen av Barndoms Uppfostran, and 144-item version of Temperament and Character Inventory). T-test/χ2-test and Binary logistic regression were used to analyze the gender differences in variables and the risk factors of online lending for males and females, respectively. Results The utilization rate of online lending exhibited a significant gender difference (p < 0.001). In addition, there were gender differences in the scores on SWLS and some subscales of C-EMBU and TCI-144. The risk factors for males’ were family members using online lending (OR = 5.527, 95% CI = 1.784–17.125) and lower scores on HA (OR = 0.938, 95% CI = 0.888–0.990). The risk factors for females’ online lending were family members using online lending (OR = 2.288, 95% CI = 1.201–4.362), hedonism (OR = 5.913, 95% CI = 1.327–26.341), and higher scores on mother’s punishment (OR = 1.099, 95% CI = 1.007–1.199). Conclusion The utilization rate of online lending in males was significantly higher than in females. More attention should be paid to gender differences and the impact of family members’ using online lending on students when intervening in online lending.